2000
DOI: 10.1681/asn.v112262
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Inhibits Macrophage-Induced Glomerular Injury

Abstract: The ability of interleukin-10 (IL-10) to inhibit macrophage recruitment, activation, and proliferation in vivo was studied in a macrophage-mediated, but T cell-independent, passive anti-glomerular basement membrane antibody-induced model of glomerulonephritis (GN) in rats. Treatment with recombinant murine IL-10 resulted in dose-dependent reductions in proteinuria (high dose: 16 ± 1 mg/24 h; low dose: 30 ± 2 mg/24 h; control treatment: 69 ± 6 mg/24 h; normal: 7 ± 1 mg/24 h) and glomerular macrophage rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Data from a study with rats that overexpressed IL-10 31 correlate with our findings that renal interstitial infiltration and renal expression of monocytes/macrophages, CD8+, and CD4+ T cells were reduced. Further studies showed that IL-10 is capable of inhibiting mesangial proliferative glomerulonephritis through inhibition of macrophage-induced glomerular injury 32,33 . MRL-Fas lpr mice with IL-10 deficiency developed exacerbated disease with heavy glomerulonephritis 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Data from a study with rats that overexpressed IL-10 31 correlate with our findings that renal interstitial infiltration and renal expression of monocytes/macrophages, CD8+, and CD4+ T cells were reduced. Further studies showed that IL-10 is capable of inhibiting mesangial proliferative glomerulonephritis through inhibition of macrophage-induced glomerular injury 32,33 . MRL-Fas lpr mice with IL-10 deficiency developed exacerbated disease with heavy glomerulonephritis 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by IL10RA is a receptor for interleukin 10 (IL-10). IL-10 is a multifunctional immune regulator in diverse inflammatory diseases, including kidney disease ( Huang et al, 2000 ; Diefenhardt et al, 2018 ). The effect of IL10RA upregulation on macrophages in glomerulopathy has not been well illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Liou and colleagues [51] evaluated Met-RANTES intraperitoneal administration in mice with neuropathic pain, and found that this treatment reduced mechanical allodynia after sciatic nerve ligation, increasing IL-10 and reducing macrophage infiltration and β-endorphin expression [51]. Increased IL-10 levels accompanied by reduced macrophage infiltration would explain the impossibility of IL-10-induced β-endorphin expression, since the same group previously showed that opioid peptides are initially secreted by neutrophils and later by macrophages [51,53,54].…”
Section: β-Endorphin Does Not Participate In Il-10-induced Antinocice...mentioning
confidence: 99%